Mosquitoes as a threat to humans and the community: the role of place identity, social norms, environmental concern and ecocentric values in public risk perception. Issue 2 (1st February 2017) - Ojala, Maria; Lidskog, Rolf
ABSTRACT: There is a risk that climate change will cause an increase of mosquito populations in Europe. Due to their nuisance to humans, there are demands to combat mosquitoes, mainly through spraying. These interventions, however, are expensive and associated with uncertainties concerning effects on biodiversity. This poses a dilemma for policy-makers, which makes it important to gain knowledge on what people's nuisance comprises. Thus, the aim of this study is to explore what factors are associated with this risk perception of mosquitoes. Theories about place identity, social norms, environmental concern and values were used to identify relevant factors. A questionnaire was distributed to 317 persons in a Swedish community where mosquitoes have increased radically. The items concerning risk perception fell out as a unidimensional scale in a principal component analysis and the internal consistency of the scale was good. Risk perception was positively related to place identity, descriptive social norms, and self-oriented environmental concern and negatively related to ecocentric values. The most important predictor was descriptive social norms, but the other factors and gender also contributed uniquely in explaining risk perception. Results are discussed in relation to the theory of social amplification of risks.